PERSEPSI SISWA TERHADAP LAYANAN INFORMASI BERBASIS MEDIA SOSIAL WHATSAPP DI SMA NEGERI 11 KOTA JAMBI - yosua harianja; Nelyahadi Nelyahadi; Hera Wahyuni (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This research was motivated by the researcher's curiosity regarding students' perceptions of WhatsApp social media-based information services because information services are core services in guidance and counseling, therefore it is important for guidance and counseling teachers to know how much benefit the use of social media has in the process of supporting service delivery. This type of research is quantitative research with a descriptive approach. The population in the study were class XI students of SMA Negeri 11 Jambi City. The sample in this study was 115 students using simple random sampling technique. The instrument used is a questionnaire. The data were analyzed using a percentage test with formula C. Based on the research results stated above, after distributing the questionnaire instrument to 115 respondents with 25 instrument items, the results showed that six indicators of students' perceptions of WhatsApp social media-based information services were in the good category. So it can be concluded that each indicator has the opportunity and potential to influence students' perceptions of WhatsApp social media-based information services at SMA Negeri 11 Jambi City